2013
DOI: 10.1371/journal.pone.0073362
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Factors Associated with Outcomes of Patients Infected with a Novel Influenza A (H7N9) Virus: A Preliminary Study

Abstract: ObjectiveThe present study aimed to analyze clinical features and factors associated with treatment outcomes of H7N9 influenza A virus infection.MethodsThe clinical progress in 18 H7N9-infected patients was monitored and recorded. The clinical features of H7N9 infection were noted and factors associated with treatment outcomes were analyzed by univariate analyses.ResultsThe average ages of patients in recovered and critical conditions were 67.0±10.83 years and 72.75±12.0 years, respectively. Renal insufficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
18
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 28 publications
6
18
0
1
Order By: Relevance
“…We found in this study that clinical complications such as ARDS, heart failure and septic shock could pose an elevated risk of death from H7N9 infection. This finding is consistent with previous studies and case reports . A longer disease duration was found to be associated with a reduced risk of death in our study.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We found in this study that clinical complications such as ARDS, heart failure and septic shock could pose an elevated risk of death from H7N9 infection. This finding is consistent with previous studies and case reports . A longer disease duration was found to be associated with a reduced risk of death in our study.…”
Section: Discussionsupporting
confidence: 94%
“…The virus has raised severe concerns due to its ability of binding to receptors in the upper respiratory tract and the high death rate in human infections. Several published studies have presented preliminary analyses of the risk factors or predictors for fatal human infections with H7N9 . However, statistical analyses, especially multivariate analyses, were underpowered in most studies due to small sample size (≤40 cases) or patients' limited epidemiological/clinical information.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the predisposing conditions for COVID19 pneumonia tended to be old age and medical comor bidities (such as chronic pulmonary disease, diabetes, and other chronic diseases), similar to previous viral infections such as influenza H7N9. 18,19 There was no obvious predilection for males or females in our cohort. However, another study reported that 30 (73%) of 41 infected patients were men.…”
Section: Figure 3: Distribution Of Various Patterns Of Lung Changes Omentioning
confidence: 60%
“…Notably, old age (≥ 65 years), male sex, medical comorbidities, and obesity have been previously identified as risk factors for the development of severe disease [2,[11][12][13][14][15]]. An age-and sex-based analysis of 63 patients infected by the H7N9 virus showed that elderly men are most commonly affected, whereas no deaths were observed in elderly women.…”
Section: Introductionmentioning
confidence: 99%